Biomechanical substantiation of mechanical impulse transfer mechanisms in the "athlete - sports equipment" system when performing moving actions in sports - Yanis Lanka; Vladimir Gamaliy; Tamara Khabinets (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to investigate mechanical impulse transfer mechanisms in the "athlete - sports equipment" system when performing moving actions in sports. Material & Methods: theoretical analysis and compilation of scientific and methodical literature and our own research results. Results: mechanism of interaction of individual body biolink's in the performance of physical exercises is studied, the basis of which is the coordination of accelerations and decelerations of the body's biolink's movement and the sequence of their incorporation into the work, which is crucial for achieving the necessary speed of the working biolink of the athlete's body when exposed to the equipment. Conclusion: mechanism of successive acceleration and successive braking of the body's biolink's in the final phase of motion ensures the transfer of the linear and rotational momentum from segment to segment, from the lower part of the body to the top and from the top to the shell, thereby informing him of the maximum speed.